Анализ требований к мониторинговой системе - Копп, В. Я.; Доронина, Ю. В. (НТУ "ХПИ", 2013)
There have been proposed methods of classification of requirements to the monitoring system on the basis of apriori correlation of estimation of realization time of requirement in course of time cycle of functioning to the monitoring system. Offered raising of task of the optimum planning of the monitoring system on condition specification of requirement.
Keywords: реинжиниринг; специфирование; сбор данных; обработка данных; классификация требований; априорное соотношение; время реализации требования; проектирование